The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s1415-47571999000400009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in five species of Anostomidae (Ostariophysi - Characiformes)

Abstract: Genetic variability was studied in five fish species (Anostomidae): Schizodon intermedius and S. nasutus and Leporinus friderici, L. elongatus and L. obtusidens, collected at one location on the Tibagi River (Paraná, Brazil). The protein data from seven systems coded collectively for 19 loci in the liver, muscle and heart. Nine of these loci were polymorphic. The estimated proportion of polymorphism loci (P) varied from 16.7% in S. intermedius to 36.9% in L. friderici; the mean heterozygosity observed (Ho) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…The A. altiparanae phenotypes we obtained for the 13 enzymatic systems studied were similar to those previously demonstrated for other Characiformes from the PR basin (Revaldaves et al, 1997;Renesto et al, 1997Renesto et al, , 2001Chiari and Sodré, 1999;Peres et al, 2002) and for Siluriformes (Almeida and Sodré, 1998;Zawadzki et al, 1999Zawadzki et al, , 2000aZawadzki et al, , 2000bRenesto et al, 2000). Our data revealed that A. altiparanae carries high genetic variability, 52.38% of polymorphic loci in PR and 38.10% in the RF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The A. altiparanae phenotypes we obtained for the 13 enzymatic systems studied were similar to those previously demonstrated for other Characiformes from the PR basin (Revaldaves et al, 1997;Renesto et al, 1997Renesto et al, , 2001Chiari and Sodré, 1999;Peres et al, 2002) and for Siluriformes (Almeida and Sodré, 1998;Zawadzki et al, 1999Zawadzki et al, , 2000aZawadzki et al, , 2000bRenesto et al, 2000). Our data revealed that A. altiparanae carries high genetic variability, 52.38% of polymorphic loci in PR and 38.10% in the RF.…”
Section: Discussionsupporting
confidence: 89%
“…The expected genetic heterozygosity was estimated as 0.1518 for the PR population and 0.0933 for the RF population, which is higher than the average of 0.051 for 195 piscine species from several world-wide localities reported in the review Genetic variability in Astyanax altiparanae 721 by Ward et al (1992) but similar to other Brazilian Characiformes. Revaldaves et al (1997) estimated that the expected heterozygosity of Prochilodus lineatus from the PR was 0.13, while Chiari and Sodré (1999) analyzed populations of five anostomid species from the Tibagi River (a tributary of the Paranapanema River) and found expected heterozygosity values of 0.142 for Leporinus elongatus, 0.132 for Leporinus frederici, 0.09 for Leporinus obtusidens, 0.092 for Schizodon nasutus and 0.072 for Schizodon intermedius. The expected heterozygosity of Hoplias malabaricus was estimated as 0.14 for both a Paraná River and a lagoon population (Peres et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2 from the third-order Paraná River tributary Ribeirão Maringá (Paiva et al, 2005). Furthermore, P. maculatus, the other long-distance migratory species analyzed in our study, showed low genetic variability (He = 0.011), contrasting with the value of He = 0.132 estimated for other migratory species such as Prochilodus lineatus (Revaldaves et al, 1997) and Leporinus friderici (Chiari and Sodré, 1999).…”
Section: Discussioncontrasting
confidence: 81%
“…This indicates that his species is undergoing a process of genetic differentiation, albeit without population structuring. A study of genetic variability between five anostomid species (Schizodon intermedius, Schizodon nasutus, Leporinus friderici, Leporinus elongates, and Leporinus obtusidens) from the Tibagi River based on iso-enzymes also recorded a high rate of polymorphism, ranging from 16.7% (S. intermedius) to 36.9% (L. friderici), reflecting high levels of differentiation (Chiari and Sodré, 1999). A second study of L. friderici based on microsatellite markers also revealed high levels of heterozygosity (0.54) and genetic diversity (0.750) (Olivatti et al, 2011), providing additional evidence for the differentiation of fishes of the genus Leporinus.…”
Section: Discussionmentioning
confidence: 94%